2004
DOI: 10.1104/pp.104.042549
|View full text |Cite
|
Sign up to set email alerts
|

AtPng1p. The First Plant Transglutaminase  

Abstract: Studies have revealed in plant chloroplasts, mitochondria, cell walls, and cytoplasm the existence of transglutaminase (TGase) activities, similar to those known in animals and prokaryotes having mainly structural roles, but no protein has been associated to this type of activity in plants. A recent computational analysis has shown in Arabidopsis the presence of a gene, AtPng1p, which encodes a putative N-glycanase. AtPng1p contains the Cys-His-Asp triad present in the TGase catalytic domain. AtPng1p is a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…It should also be noted that while the orthologues of cytoplasmic PNGases have been found in plants through database survey [20,116], and indeed a PNGase-deglycosylated form has been observed during ERAD in plant cells [117], the direct proof of the cytoplasmic PNGase activity in Png1p-orthologue has not yet been provided. It is noteworthy that the orthologue of cytoplasmic PNGase in Arabidopsis thaliana, AtPng1p, exhibits transglutaminase activity [118]. Indeed the Png1p and transglutaminases share the homology around catalytic triad [37,119].…”
Section: Free Oss In Plantsmentioning
confidence: 99%
“…It should also be noted that while the orthologues of cytoplasmic PNGases have been found in plants through database survey [20,116], and indeed a PNGase-deglycosylated form has been observed during ERAD in plant cells [117], the direct proof of the cytoplasmic PNGase activity in Png1p-orthologue has not yet been provided. It is noteworthy that the orthologue of cytoplasmic PNGase in Arabidopsis thaliana, AtPng1p, exhibits transglutaminase activity [118]. Indeed the Png1p and transglutaminases share the homology around catalytic triad [37,119].…”
Section: Free Oss In Plantsmentioning
confidence: 99%
“…The most studied plant gene coding for a protein with TGase activity is Arabidopsis AtPng1p . AtPng1p is constitutively expressed at low levels in all plant organs during various stages of development and under various light conditions (Della Mea et al 2004b). Similar expression pattern was found for the HvPng1 - like homolog in barley.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the plant cytoplasmic PNGase may have followed a distinct evolutional route from others to acquire its unique function. Interestingly, AtPng1 was reported to possess TGase activity [171], besides PNGase activity [172], in vitro. However, the functional role of AtPng1, in vivo, remains poorly understood.…”
Section: Occurrence Characteristics and Functions Of Pngasesmentioning
confidence: 99%